Electrostatic analysis of transmission lines to simulate corona discharge at high voltage - (:unkn) unknown (My University, 2011)
This paper presents the results of Boundary Element Method (BEM) numerical procedures of voltages distribution between transmission lines in order to investigate the theoretical corona discharges. The algorithm of the voltage distributions are coded in Mathematica studying size of the system under controlling Neumann and Dirichlet boundary conditions. Conducting experimental work at a high voltage (HV) is potentially very dangerous. Therefore, simulation is a vital research approach, and computer modeling offers significant advantages to estimate optimal calculation over established system to prevent dangerous voltage and not to exceed the corona voltage. In this paper, the BEM results are verified with Finite Element Methods (FEM) which is coded in Mathematica too.